Religion and Education as Shaping Factors in Managerial Decisions: A Case Study on the Main Religious and Irreligious Groups in Romania - Iustin Cornel Petre (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics)
This study statistically analyzes data provided by the National Institute of Statistics on the national distribution of Romanians' educational achievement in formal education structures: primary, secondary and university, according to their religious or irreligious affiliation. Religious groups: Orthodox, Roman Catholic, Greek Catholic, Reformed, Pentecostal, Adventist, Baptist and Muslim, and irreligious groups: atheist, agnostic and non-religious, i.e. those groups that refuse any religious belief or practice. The method used is factorial correspondence analysis. The objective of the research is to scientifically validate the existence of significant differences between religious and irreligious groups in Romania in terms of education, and to show how these differences influence differently the behaviors of decision makers in business management. The results showed that religious and educational diversity in Romania also results in a varied shaping of organizational cultures through specific traditional values and beliefs that play a central role in the way human resources and managerial decisions are managed. Religious groups with an emphasis on traditions, such as Orthodox, Roman Catholic, Greek Catholic, Reformed, Pentecostal, Adventist, Baptist and Muslim, tend to prefer hierarchical, conservative, community-oriented and inclusive organizational structures. In contrast, less traditional groups such as agnostics, atheists and the religiously non-religious will prefer a rational, flexible and open approach to management, influenced by liberal values, meritocracy and individualism.